1 PENGARUH FASILITAS WISATA TERHADAP KEPUASAN PENGUNJUNG KE OBJEK WISATA AIR TERJUN BAYANG SANI KABUPATEN PESISIR SELATAN - Gusneli, Gusneli; Silfeni, Silfeni; Kasmita, Kasmita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
The purpose of this research is to examine the influence between the facility on the tourism object towards visitor satisfaction in Air Terjun Bayang Sani, Pesisir Selatan Distric. The type of research is clausal assosiative. Population in this research are amounted to 3.720 people. The sampling technique is non probability sampling, by using insidental sampling. Sample in this research are amounted to 97 people. Data collecting using a questionnaire that has been tested for validity and reliability. Based on the result of the research, show that most of all the facility on the tourism in Air Terjun Bayang Sani is good (53,60 %), and also for visitor satisfaction in Air Terjun Bayang Sani exist on enough category (60,82 %). The result also indicate that the are significant influence between facility on the tourism and visitor satisfaction in Air Terjun Bayang sani value is 7,3% while 92,7% are influenced by other factors with the coefficient determinant (R Square) value is 0,270 and the significant value is 0,008. Key Words: Facility on the Tourism and Visitor Satisfaction